Plan de negocios para la implementación de una empresa de agua purificada en el Cantón Yantzaza, Provincia de Zamora Chinchipe - Tituana González, Francisco Armando (2015)
This is a Business Plan that took place in the Yantzaza canton Zamora-Chinchipe province, in order to analyze the feasibility of putting a company of purified water of quality, that contribution to maintain the health of consumers and to promote industrial activity that generates direct and indirect job opportunities. The business is based on the production and sale of purified water without gas directed to human consumption, given that the product is classified in the Group of high risk foods, are considered the aspects required to offer a product that complies with Ecuadorian technical NTE INEN 2200:2008 water purified bottled. The plant would be located in the Yantzaza canton with coverage for the cantons of El Pangui and sentry from the Condor. Market goal there are several brands of bottled water, customers are not necessarily inclined for a lower price but for the perception of the quality. Therefore our product will differentiate by quality and service, offered in presentations bottle ½ l, 1 l, 4 l and 20 l., and will be available at the points of sale. According to the perspective of the market and on the basis of financial analysis, intends to achieve a goal in sales of 40 to 45% of the market, earning $66590 at the end of the first year, given the excellent purchase intent. The economic indicators are positive, indicating that the project is viable from the economic and financial perspective therefore determines that it is feasible to invest in the present proposal.